DIPLOMATIC DYNAMICS: KOREA AND AFRICA IN THE COLD WAR CONTEXT - Hyomin Jung (Asian and African Studies)
This article examines the diplomatic strategies of South and North Korea in Africa during the Cold War, focusing on the ideological stances of African countries and economic diplomacy. Using official documents from South Korean ministries and North Korean publications, the research analyses diplomatic ties and economic support to African countries. In the early 1960s, the political orientations of newly independent African nations heavily influenced diplomatic relations with both Koreas. In the 1970s, African countries shifted to prioritising a third world identity, such as the Non-Aligned Movement, over ideology. Both Koreas used economic diplomacy, offering financial and material support. However, in the mid-1970s, North Korea gained an advantage by joining the Non-Aligned Movement. South Korea lagged behind North Korea until the 1970s, but in the 1980s, its growing economy helped it catch up in diplomatic relations. This research contributes to an understanding of the evolving diplomatic orientations of the two Koreas and African countries by analysing the role of economic diplomacy.